2022
DOI: 10.1155/2022/2673740
|View full text |Cite
|
Sign up to set email alerts
|

Practice towards Hepatitis B Virus Infection Prevention and Its Associated Factors among Undergraduate Students at Hawassa University College of Medicine and Health Sciences, Hawassa, Sidama, Ethiopia, 2021: Cross-Sectional Study

Abstract: Background. Hepatitis B virus infection is a major global health burden accounting for 2.7% of all deaths globally. Being part of the health care system, the risk of exposure to hepatitis B viral infection among medical and health science students is found to be high. In Ethiopia, particularly in this study area, very little is known about the practice of students towards hepatitis B virus infection prevention and its associated factors. Objective. The aim of this study was to assess the practice towards hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…These practices reflect their commitment to maintaining infection control measures and their personal safety. Of particular significance is the high vaccination rate, which not only safeguards healthcare workers but also prevents them from becoming carriers and potentially transmitting the virus to patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…These practices reflect their commitment to maintaining infection control measures and their personal safety. Of particular significance is the high vaccination rate, which not only safeguards healthcare workers but also prevents them from becoming carriers and potentially transmitting the virus to patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study revealed that participants in the 19 to 20 (younger) age group demonstrate a higher likelihood of poor practice in the prevention of HBI in contrast to those in the 23 to 24 (elderly) age group. A study conducted in Ethiopia [ 38 ] refutes our finding; they found that elderly students were more likely to have poor practice than younger students. These discrepancies are most likely due to the variations in the focus on different target group.…”
Section: Discussionmentioning
confidence: 46%
“…The knowledge levels in study are much lower than in previous studies conducted in Iran (90%), Vietnam (79.3%), and western Ethiopia (86.2 %). [28][29][30] However, it was higher than reports from Ghana (63.9.5%) and Malaysia (50.3%). 31,32 The inclusion of both medical and non-medical students in our current study, as well as differences in the knowledge evaluation questions, could explain the discrepancy.…”
Section: Discussionmentioning
confidence: 55%